ANALISIS PSYCHOLOGICAL CAPITAL, MINDFULNESS DAN EMOTIONAL INTELLIGENCE TERHADAP KINERJA KARYAWAN INDUSTRI JASA - Kushariyadi Kushariyadi; Jean Evelyn Ilela; Mozart Malik Ibrahim; Fanny Patricia Teng; Basuki Wisnu; Fatimah Malini Lubis (JURNAL LENTERA BISNIS, 2025)
Employee performance in the service sector is the intended focus of this research into the relationship between psychological capital, mindfulness, and emotional intelligence. Emotional and psychological aspects significantly impact how well employees perform in fast-paced, high-pressure workplaces. A person's psychological capital encompasses their optimism, self-assurance, hope, and perseverance in the face of adversity at work. Workplace attention and adaptability are both enhanced by practicing mindfulness, which is associated with being fully present in the here and now. The capacity to be self-aware, emotionally intelligent, and socially adept is a key component of emotional intelligence. A quantitative approach was used in this investigation, employing a survey procedure that included 200 employees. A positive and statistically significant relationship between employee performance and the three variables was found in the study. Among these factors, Psychological Capital, Emotional Intelligence, and Mindfulness have the most impact. According to these results, service sector companies can maximize employee performance by employing a human resource management strategy that takes into account employees' psychological and emotional needs.